Detection of environmental SARS‐CoV‐2 RNA in a high prevalence setting in Spain. Issue 3 (24th September 2020) - Fernández‐de‐Mera, Isabel G.; Rodríguez del‐Río, Francisco J.; de la Fuente, José; Pérez‐Sancho, Marta; Hervás, Dolores; Moreno, Inmaculada; Domínguez, Mercedes; Domínguez, Lucas; Gortázar, Christian
Abstract: Since March 2020, Spain (along with many other countries) has been severely affected by the ongoing coronavirus disease 19 (COVID‐19) pandemic caused by the rapid spread of a new virus (severe acute respiratory syndrome coronavirus 2; SARS‐CoV‐2). As part of global efforts to improve disease surveillance, we investigated how readily SARS‐CoV‐2 RNA could be detected in environmental samples collected from an isolated rural community in Spain with a high COVID‐19 prevalence (6% of the population of 883 inhabitants). The first diagnosis of COVID‐19‐compatible symptoms in the village was recorded on 3 March 2020, and the last known active case resolved on 5 June 2020. By 15 May, two months after strict movement constraints were imposed ('lockdown'), and the cumulative number of symptomatic cases had increased to 53. Of those cases, 22 (41%) had been tested and confirmed by RT‐PCR. On 13 May and 5 June, samples were collected from high‐use surfaces and clothes in the homes of 13 confirmed cases, from surfaces in nine public service sites (e.g. supermarket and petrol station) and from the wastewater of the village sewage system. SARS‐CoV‐2 RNA was detected in 7 of 57 (12%) samples, including three households and three public sites. While there is not yet sufficient evidence to recommend environmental surveillance as a standard approach for COVID‐19 epidemiology, environmental surveillance research may contribute to advance knowledge about COVID‐19 by further elucidating virus shedding dynamics and environmental contamination, including the potential identification of animal reservoirs.